Impacts of digitalization on foreign investments in the European region during the COVID-19 pandemic - Le Thanh Ha; Nguyen Thi Thanh Huyen (Development Studies Research, 2022)
The inflow of foreign direct investment (FDI) worldwide, especially in European countries, suffered a steep fall due to the rapid spread of the COVID-19 virus. This article is the first effort to empirically investigate the nexus between digital transformation and FDI inflows, thereby finding a way to help countries overcome the current situation. Using the data of 23 European countries pre-COVID (2015–2019) and during the COVID health crisis (2020), we demonstrate a nonlinear relationship between digitalization and FDI inflows, implying that a certain extent of digital transformation could promote the inflows of FDI. Before the COVID-19 health crisis, digital business played a critical role in attracting FDI inflows. E-commercial activities also enhanced FDI flows during the spread of the COVID-19 pandemic, and digital public services may be an effective tool to help countries overcome the health crisis. Furthermore, digitalization plays a critical role in promoting FDI inflows in both the short term and long term. Hence, digital transformation is an inevitable process that countries need to embrace in order to overcome the challenges of the COVID-19 pandemic and resolve the delay or lack of foreign investments.